Assess community strength and needs to create an effective community-based education for living heritage conservation in Melaka world heritage site - Abdul Aziz, Noor Azramalina; Mohd Ariffin, Noor Fazamimah; Ismail, Nor Atiah; Ismail, Sumarni; Alias, Anuar (Human Resource Management Academic Research Society, 2022)
Living Heritage or intangible cultural heritage is defined as human skills and knowledge, practices, expression, and instruments that form the transmitted practices of local people. Threatened by globalization and cultural modernization, many emotions and manifestations of Intangible cultural heritage are in crisis because of the lack of responsibility, recognition, awareness, and education in the community. Using the community-based education principal model, the information-based community will be identified in this study to assess Community strength and needs before planning the action for quality and effective community-based education for living heritage conservation.